Winning with words : the origins and impact of political framing - Schaffner, Brian F.; Sellers, Patrick J. (Routledge, 2010)
"This text brings together prominent scholars from political science, communication, and psychology in a tightly focused analysis of both the origins and the real-world impact of framing. Across the chapters, the authors discuss a broad range ofcontemporary issues, from taxes and health care to abortion, the death penalty, and the teaching ofevolution. The chapters also illustrate the wide-ranging relevance of framing for many different contexts in American politics, including public opinion, the news media, election campaigns, parties, interest groups, Congress, the presidency, and the judiciary."--BOOK JACKET.